Zrównoważony rozwój rolnictwa zintegrowanego = Suistainable development of integrated agriculture - Małecki, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article described origin of equable development, its essence, rights, principles and program as well as features of equable development and integrating agriculture.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)